2015
DOI: 10.1902/jop.2014.140152
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Best Predictor for Oral Cleanliness After Brushing? Results From an Observational Cohort Study

Abstract: Evenness of distribution of brushing time and duration of circling movements are aspects of observed habitual brushing behavior that predict brushing capabilities in terms of oral cleanliness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
29
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 17 publications
6
29
1
Order By: Relevance
“…Second, periodontal status was assessed as pocket depth, which T A B L E 2 Brushing twice a day or more often at baseline (2000) and follow-up (2011), by baseline characteristics (n = 1,025) Third, information on toothbrushing behaviour was collected through self-reports. Although some might argue that dental plaque indices provide a stronger assessment of oral cleanliness, there is evidence of good correlation between self-reported toothbrushing frequency and oral hygiene indices (Gil et al, 2015;Harnacke et al, 2015). More importantly, current recommendations on plaque control and oral hygiene maintenance are based on habitual toothbrushing behaviour, not clinical levels of dental plaque.…”
Section: Discussionmentioning
confidence: 99%
“…Second, periodontal status was assessed as pocket depth, which T A B L E 2 Brushing twice a day or more often at baseline (2000) and follow-up (2011), by baseline characteristics (n = 1,025) Third, information on toothbrushing behaviour was collected through self-reports. Although some might argue that dental plaque indices provide a stronger assessment of oral cleanliness, there is evidence of good correlation between self-reported toothbrushing frequency and oral hygiene indices (Gil et al, 2015;Harnacke et al, 2015). More importantly, current recommendations on plaque control and oral hygiene maintenance are based on habitual toothbrushing behaviour, not clinical levels of dental plaque.…”
Section: Discussionmentioning
confidence: 99%
“…A dimension of mouthwash was not included for two reasons: it is not a basic, but a complementary recommendation 8,12 , and to prevent that lowincome people get a low score as a result of not being able to follow this complementary or additional recommendation. …”
Section: Design Of the Measuring Instrumentmentioning
confidence: 99%
“…It also recommends the use of mouthwash as part of routine hygiene habits, and changing toothbrush every four months or sooner 8,9 . The effectiveness of dental cleaning correlates with brushing time and not with the use of toothpaste [10][11][12] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…If people follow the scientific method strictly to brush the teeth every time, using manual toothbrush can achieve good cleaning effect as well, however, studies have shown that the majority of people did not brush their teeth systematically, the plaque removal capability of people still tend to be low [41][42][43][44][45][46] , and brushing teeth incorrectly was particularly common in children [47][48][49] . Moreover, it should be noted that receiving oral health instruction could improve the effect of powered toothbrush and manual toothbrush on plaque removal 50 , thus, it is necessary for the public to receive enough instructions from doctors to master the systematical skills of tooth brushing and be aware of the tools which may make tooth brushing more effective.…”
mentioning
confidence: 99%